Malaysian Consumers’ Shopping Behaviour After the First Phase of Movement Control Order (MCO) Announcement - Khairunesa ISA; Nurliyana ROSNI; Azmi ABDUL LATIF; Sarala Thulasi PALPANADAN (Communications of International Proceedings, 2021)
The annoucement of the restrited movement control due to the COVID-19 pandemic could bring food shortage fear among the netizens. Thus, this paper presents the descriptive data and analysis on goods purchasing behaviour among consumers immediately after the announcement of the first phase of Movement Control Order (MCO). A survey was conducted throughout the country including Sabah and Sarawak using an open-ended questionnaire that was distributed online. A quantitative method with a descriptive research design was adopted to explore insights obtained from the  data collected in relation to the objective of the research. A total number of 485 adults from 14 states provided valid responses to the online questionnaire. Primarily, the questionnaire solicited open-ended responses about the participants’ involvement pertaining to goods purchasing activities and items that they prioritized in purchasing when the first MCO was announced. In conclusion, the findings provided an initial record of the important goods that consumers looked for that they felt could help them to survive during the MCO period.
Keywords: Movement Control Order; panic buying; purchasing activities; World Health Organization.